Integrating Metaverse in Psychiatry for Adolescent Care and Treatment (IMPACT) - Faisal A. Nawaz; Richard Mottershead; Rihab Farooq; Jaroslaw Hryniewicki; Michael Kaldasch; Ben Jelloul El Idrissi; Hanaa Tariq; Waleed Ahmed (Digital Health)
The integration of the metaverse in healthcare has been evolving, encompassing various areas such as mental health interventions, neurological treatments, physical therapy, rehabilitation, medical education, and surgical procedure assistance. For the adolescent population, growing in the digital era and witnessing the interaction of technology with daily life has made digitalization a second nature. Despite the potential of this technology in advancing adolescent mental health care and treatment, there is a notable gap in research and development. Thus, this commentary article aims to elucidate the current landscape of emerging technologies for adolescent mental healthcare in the metaverse, identify potential challenges with its implementation in this growing population, as well as provide recommendations to overcome these obstacles.